(untitled) (Research, Society and Development, 2023)
Apocrine duct adenocarcinoma is a poorly reported type of a sweat gland neoplasia. In this paper, we describe the case of a dog, six years old, attended at the Veterinary Medicine Hospital of Universidade Federal Fluminense (HUVET-UFF) with ulcerated and circular lesions on the skin of the neck, thoracic limb and right hemithorax. Previously, in another clinic, the dog received the wrong diagnosis of sporotrichosis, performed through cytopathology only and submitted to standard therapy with antifungal that did not result in any improvement. In the HUVET-UFF, additional tests were performed, including biopsy of lesions for fungal culture and histopathology. The culture was negative for sporotrichosis and the histopathological examination described the alterations characterizing the disease not as a fungal disease, but as a micropapillary ductal apocrine adenocarcinoma, a malignant neoplasm, already at an advanced stage of development and that rapidly caused the death of the patient. Therefore, this study aimed to report the occurrence of this distinct pattern of adenocarcinoma of the apocrine duct in a dog that initially resembled the clinical manifestation of sporotrichosis and that, if it had been correctly diagnosed and treated without delay, could have resulted in a longer survival for the patient.